Aplikabilitas Metode Applied Behavior Analysis untuk Mengurangi Perilaku Anak ADHD (Attention Deficit Hyperactivity Disorders) - Marlina Marlina (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2018)
Abstract: Children who have attention deficit hyperactivity disorders (ADHD) often refered to as a hyperactive child. Children who have behavioral disorders generally have normal intelligence levels, but because the disorder, they show underchiever. This is because they are difficult to focus, concentrate, obey school rules, sit still in class (do not move the seat), and so forth. Applied behavior analysis methods can be used as an approach to solve the problem above. The approach used in the modification of behavior include: relaxation, systematic desensitization, sensitivity training, imitation through resistence. Of some of these approaches that are often used to change behavior inADHD children is imitation through modeling, operant conditioning, immunization techniques, and assertiveness training. Keywords: Apllied behavior analysis and hyperactivity.